WHY MYRINGOPLSTIES FAIL? IMPACT OF RELEVANT CLINICAL FACTORS ON THE SURGICAL OUTCOME; A STUDY FROM PAKISTAN - Niazi, Saleem Asif; Khattak, Shahid Farooq; Atif, Khoala KHan; Rafique, Atif; Gohar, Mohammad Shahid (Journal of Ayub Medical College Abbottabad, 2021)
Background: Myringoplasty is the reconstruction of the tympanic membrane by grafting. Success varies from 50-100%. A study was conducted to unveil the vital causes for failed myringoplasty with an aim to attenuate graft rejections and augment better outcomes. Methods: It was descriptive case series in which data was retrospectively collected at a tertiary care hospital (Rawalpindi, Pakistan) from January 2009 to December 2018. First 600 consecutive patients who qualified for inclusion/ exclusion criteria, underwent myringoplasties were followed-up for 06 months. Graft Take/Failure, the main outcome variable, was correlated with relevant independent variables. Data was collected on a structured pro forma, approved by hospital ethical committee. Data was analysed using IBM-SPSS-21.0. Results: Out of 600, 164 (27.3%) had graft rejection; failure being significantly enhanced by increasing age (p<0.001), larger perforation (p-0.025), co-morbidities (p<0.001), especially diabetics (p=0.040) and Eustachian tube (p-0.016) dysfunction amongst among systemic and ENT diseases respectively, and discharge-free ear (Dry Ear) for <4 weeks (p<0.001); while best graft take was achieved with end-aural surgical technique (p=0.048). Gender (p-0.897) did not caste a significant impact on graft outcome. Conclusion: The results of various surgical approaches of myringoplasty are equitable. Proper socio-demographic and clinical evaluation can improve graft outcome, and this surgery shall be discouraged in patients with diabetes mellitus and defective Eustachian Tube functions.